2007
DOI: 10.1161/hypertensionaha.106.081083
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity and Guanosine 3′,5′-Cyclic Monophosphate Activating Actions of Various Molecular Forms of Human B-Type Natriuretic Peptide

Abstract: Abstract-Recent studies support the speculation that different molecular forms of the cardiac hormone BNP with differential biological activity may circulate in heart failure and be detected by conventional assays. In the current study we determined the ability of 3 widely used conventional assays to detect these different forms thought to circulate in heart failure. We also evaluated the ability of pro-BNP (1-108), N-terminal peptide (NT)-pro-BNP (1-76), and BNP 3-32, the latter a cleavage product of BNP 1-32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 23 publications
2
106
0
1
Order By: Relevance
“…Unprocessed proBNP has markedly reduced, if any, hormonal activity (35,36 ). The presence of unprocessed prohormone in the blood of HF patients suffering from insufficient natriuresis and diuresis remains an unexplained phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Unprocessed proBNP has markedly reduced, if any, hormonal activity (35,36 ). The presence of unprocessed prohormone in the blood of HF patients suffering from insufficient natriuresis and diuresis remains an unexplained phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…ProBNP is a poor stimulator of guanylyl cyclase. There are differential cGMP activating properties of BNP forms and, notably, proBNP 1-108 and NT-proBNP 1-76 have reduced cGMP activity in vitro (29 ). Some speculate that unprocessed proBNP is a circulating "reserve" of BNP since in vivo cleavage of proBNP produces BNP.…”
Section: Probnp and Cross-reactivitymentioning
confidence: 99%
“…While the first generation of NT-proBNP immunoassays uses polyclonal antibodies to amino acids 1-21 and 39 -50, the second generation uses monoclonal antibodies (MAb) recognizing the central region of NTproBNP: amino acids 22-28 and 42-46 (27)(28)(29)(30)(31). Many studies have demonstrated the negative effect of glycosylation for antibody recognition to the middle area of the NT-proBNP molecule.…”
Section: Nt-probnp Assaysmentioning
confidence: 99%
“…Increasing attention on proBNP has occurred based on reports that it is increased in the plasma of humans with advanced heart failure (HF) (11,12 ). Further, recent studies have reported that circulating corin is reduced in human HF, advancing the concept that increased proBNP in human HF, which is recognized by conventional BNP assays and has reduced cGMP actions, is a result of a corin deficiency (12)(13)(14).…”
Section: B-type Natriuretic Peptide (Bnp)mentioning
confidence: 99%